Potential and constraints - Stanbury, Lloyd A.W. (CCS GeorgetownGY, 1994)
Sees the products of Caribbean cultural expression as providing a real option for economic development if tackled with proper research and planning. Suggests that this task requires the input of both government and the private sector. Argues that a planned programme for the development of culture as a viable vehicle within the productive sector, would have to address issues such as, education and training; marketing; promotion; product development; and a legal and administrative framework within to operate.